A SPECIAL STUDY OF GUIDANCE IN ISLAMIC TEACHINGS FOR MUSLIM YOUTH TO AVOID MISUSE OF SOCIAL MEDIA: https://doi.org/10.5281/zenodo.17295333 - Dr. Abdul Rahman (Journal of Religion and Society, 2024)
The 21st century's digital landscape, dominated by platforms like TikTok and Instagram, presents significant challenges and spiritual temptations (Fitnah) to Muslim youth. While technology facilitates communication and offers benefits, the negative impacts of social media are seen to outweigh the positive, dangerously affecting the spiritual, psychological, and social well-being of the younger generation and specifically targeting their faith (Iman). This article asserts that Islam, as a complete and comprehensive code of life provided over 1400 years ago, serves as the essential shield and source of guidance for navigating these modern digital challenges. It explores the ideal attitude of a Mu'min (true believer) in times of Fitnah, emphasizing steadfastness on the Quran and Sunnah, adherence to the methodology of the Companions, creating awareness, and acting with wisdom. Furthermore, the paper provides core Islamic guidelines for Muslim youth to effectively and responsibly use social media. These guidelines include maintaining consciousness of Allah (Taqwa), ensuring pure intention in digital activities, upholding modesty (Haya), verifying information to combat fake news, utilizing social media for good purpose and Da'wah, and guarding against time wastage and cyberbullying. By adhering to these timeless principles and idealizing the life of the Prophet Muhammad (peace be upon him) and the righteous predecessors, Muslim youth can transform social media from a source of punishment and temptation into a tool for salvation and positive global engagement, thereby protecting their faith and benefiting the Muslim Ummah. Keywords: Islam, Social Media, Fitnah, Muslim Youth, Haya